Multilingualism and the role of sibling order - Kinsella, Benjamin (Brill, 2020)
Acknowledgments – List of Figures and Tables – 1 Introduction – Theoretical Background: Child Bilingualism and the Role of Sibling Order in Heritage Language Maintenance – Introduction – 1 Linguistic Outcomes Related to Child Heritage Speakers – 2 Language Socialization Practices and Family Language Policy – 3 The Role of Birth Order in Multilingual Families – 4 The Current Study – 2 Local Context and Methods – 1 Local Context of NJ Latino Community – 2 Participants of the Current Study – 3 Summary of Protocols – 4 Data Analysis – 5 Researcher Positionality – 3 Siblings' Language Use Patterns – Connections between Linguistic Domains – Introduction – 1 Siblings' Language Background and Reported Proficiencies – 2 Results from Expressive Vocabulary Assessments – 3 Siblings' Oral Narratives in Spanish – 4 Conclusions – 4 Siblings' Language Ideologies and Identities – Introduction – 1 Siblings' Language Ideologies in Support of Bilingualism – 2 Siblings' Negative Language Ideologies toward Bilingualism – 3 Siblings' Language Identities and Group Memberships – 4 Conclusions – 5 Siblings' Language Practices in the Home and Community – Introduction – 1 The Home Language Practices of Daniel and Mia (Family 1) – 2 The Home Language Practices of Brent and Kyle (Family 2) – 3 The Home Language Practices of Benito and Oscar (Family 3) – 4 The Home Language Practices of Samuel and Kendra (Family 4) – 5 The Home Language Practices of Lani and Leo (Family 5) – 6 The Home Language Practices of Bryce and Melvin (Family 6) – 7 Conclusions – 6 Siblings' Language Practices in the School – Introduction – 1 The School Language Practices of Daniel and Mia (Family 1) – 2 The School Language Practices of Brent and Kyle (Family 2) – 3 The School Language Practices of Benito and Oscar (Family 3) – 4 The School Language Practices of Samuel and Kendra (Family 4) – 5 The School Language Practices of Lani and Leo (Family 5) – 6 The School Language Practices of Bryce and Melvin (Family 6) – 7 Conclusions – 7 Conclusion – Rethinking Heritage Language Maintenance in the U.S. – Introduction – 1 Summary of Findings – 2 Discussion – 3 Limitations and Directions for Future Research – Appendix – References – Index. Based on a multi-year ethnography in one Spanish-speaking community in New Jersey, this book is a meticulous account of six Mexican families that explores the relationship between siblings' language use patterns, practices, and ideologies. Combining insights gained from language socialization and heritage language studies within the larger field of sociolinguistics, the book's findings examine siblings' sociolinguistic environments and the ways in which these Latino children use and view their multilingual resources in the home, school, and broader community. This study emphasizes the links between siblings' language ideologies, agentive decision making, and linguistic patterns, and the ways in which birth order influences the different dimensions of heritage language maintenance in the U.S
10.1163/9789004439115
Keywords: Bilingualism in children; Mexican American youth; Brothers and sisters; Heritage language speakers